Egg Parasitoid, Trichogramma and its Host Range in India - Ahmad, Mukhtar; Jamal Ahmad, M. D.; Mishra, R. K.; Khan, H. R. (Indian Forester, 2002)
Trichogramma species so far recorded from India include T. acheae, T. agriae, T. australicum, T. brevifringiata, T. chilonis, T. chilotraeae, T. embryophagum, T. flandersi, T. hesperidis, T. japonicum, T. minutum, T. pallidiventris, T. plasseyensis, T. poliae, T. pretiosum, T. raoi and T. semblidis. These were recorded from different States including Andhra Pradesh, Bihar, Gujarat, Himachal Pradesh, Jammu and Kashmir, Karnataka, Orissa, Punjab, West Bengal, Uttar Pradesh and Uttaranchal parasitising upon variety of insect pests of forestry, agriculture, and vegetable crops.